HARMONISASI KELUARGA PASANGAN SUAMI ISTRI YANG TIDAK MEMILIKI KETURUNAN DI DESA BANGUN JAYA KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Yani, Irma; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Harmonious families are families who always understand each other's flaws and also respect each other's personalities. Not having offspring in marriage is a difficult thing. Because the child is the hope of the child's family has meaning and function for the family. This study aims to see how married couples keep harmony in their family. To realize a harmonious family there are several ways, namely: the existence of mutual understanding, accept each other reality, foster love, implement the principle of mutual consultation, forgive each other and participate in common progress. The purpose of this study is to see what the dynamics of life they pass through this couple and how to solve family problems without any children make the family always harmonious. The method used is qualitative descriptive approach. From the results of this study can be concluded that the absence of children in married couples is not a factor for the family is not harmonious in marriage. The situation was seen in married couples who still survive and harmonious household with a relatively long marriage age. This research uses the theory of funsional and family theory which in it there is a family function in an effort to maintain the harmonization of married couples who have no offspring in the village of Bangun Jaya Kecamatan Tambusai Utara Kabupaten Rokan Hulu.Keywords: harmonious family, family without children, family dynamics, family functions.